The Evaluation of Functional Performance of National Roadway using Three Types of Pavement Assessments Methods. (2017) - Suryoto,; Siswoyo, Dendy Paramaartha; Setyawan, Ary
Abstract: The road section of Palur-Sragen-Mantingan categorized as a national road and serve 43.00 km long arterial road, is the part of the middle lane that connects the important cities in Java Island. The damage that frequently occurs will certainly affect the safety and comfort of road users. Road surface condition assessment is one step to determine the type of program evaluation needs to be done. This study aims to determine the functional condition of the road by three methods and to assess the closeness of the relationship between these three methods. The descriptive study is carried out to conduct the comparability of the road condition assessment data resulted from three methods for analyzing the results of the assessment of road conditions between the years of 2011-2013. The assessment method of road conditions consists of the International Roughness Index, the Pavement Condition Index and the Surface Distress Index. The correlation between these methods were obtained from the Pearson correlation analysis based on CurveExpert program. The results showed that the linear regression analysis between the methods of IRI and PCI showed the value of PCI=0.966+10.919IRI, it means there is a positive correlation between the two methods and the r value is 0.976 indicates a very close correlation between the two methods. IRI and SDI method show the value of SDI=32.684+3.355IRI, it means a positive correlation between the two methods and the r value is 0.203 indicates a poor relation between the two methods. PCI and SDI method show the value of SDI=18.023+0.592PCI, it means there is a positive correlation between the two methods and the r value is 0.381 indicates a poor relation between the two methods. Limited from this research, the conclusion could be drawn that the different method of functional measurements could potentially result in the different pavement index, consequently the different decision for pavement and rehabilitation scheme.